Modeling of molecules in circumstellar media - Vallverdú, Rodolfo Enrique (2021)
B[e] stars are characterized by having spectral lines in emission, both of forbiden and allowed transitions, produced in the disk that surrounds the star. The temperature and density conditions in these disks allow the formation of molecules, whose presence is manifested in the observation of molecular bands in emission. In this work we present the code that we have developed which allows us to model the emission bands of different diatomic molecules, such as CO, SiO, CS, SiS, NH, etc. The program takes into account the different isotopes that make up the molecules, since these significantly affect the bands. With this program we can obtain the combined spectra of molecules composed of different isotopes and the superposition of different molecules. Comparing with the observations, we can use these theoretical spectra not only to determine the presence of the molecules, but also other parameters, such as the temperature and density of the regions of formation of the molecules in the disk, the velocity of rotation, and the region of the disk where the molecules are found. We can also use them to determine the abundance ratio of the different isotopes of a molecule, which can be used to determine the evolutionary stage of the star.